Effect of chitin and chitosan on the biosynthesis of rutin in shoot cultures of Ruta graveolens L. - Hussain, Malik Aabid; Nathar, Varsha Nitin; Mir, Javid Iqbal; Mushtaq, Roohi (Current Botany, 2025)
The objective of the present study was to study the effect of biotic elicitors (chitin and chitosan), to enhance the production of flavonoid rutin in shoot cultures of Ruta graveolens L. The in vitro shoots were cultured on solid and liquid medium augmented with different concentrations of chitin and chitosan (0, 0.01%, 0.1% and 0.5%). The highest content of rutin (38.11±0.77 mg/g DW) was shown by shoot suspension cultures cell line fortified with 0.1% chitin and the lowest rutin content (14.44±0.86 mg/g DW) was observed in cell line supplied with 0.5% chitin. The maximum fresh weight 167.23±1.66 g/L and dry weight 17.36±0.55 g/L was also observed at same concentration of chitin. While in the case of chitosan, the maximum content of rutin (36.75±0.75 mg/g DW) was shown by shoot suspension culture cell line fortified with 1.5 mg/L BAP (6-Benzyl amino purine)+1.0 mg/L IBA (Indole-3-butyric acid) and 0.1% Chitosan. The rutin content increased by increasing the concentration of chitin and chitosan from 0.01% to 0.1% but further increase (0.5%) of the elicitor showed decrease in rutin content but still above the level of the control cell line. These results clearly suggest that both the biotic elicitors can enhance the production of rutin in shoot cultures but chitin at 0.1% w/v induced maximum production.